Peran pemerintah desa dalam pemberdayaan perempuan dibidang kesejahteraan keluarga (PKK) - Miftahul Jannah, Miftah (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2022)
This study aims to determine the role of the village government in empowering women in the field of family welfare empowerment (PKK) in Air Balui Village, Musi Banyuasin Regency. The type of research used in this study is a descriptive qualitative method. Data collection is primary data. The subjects of the study were the village head, women in the field of family welfare empowerment chairman, women in the field of family welfare empowerment members and the community. Data analysis using Miles and Huberman consists of three stages, namely: data reduction, data presentation, and drawing conclusions. The results of this study can be concluded that the village head has done his role by empowering women through women in the field of family welfare empowerment happiness. The program has been carried out well, and the head of Balui Water Village supports the planned program. For the women in the field of family welfare empowerment chairman and village head, they can succeed in programs, especially increasing handicraft output. The village head has carried out planning and implemented improvement programs in improving creative ideas through the form of training, the training carried out is expected to improve the economy of the residents of Air Balui village. The assessment of the village head can be analyzed that the village head has been good in implementing women's empowerment programs through women in the field of family welfare empowerment activities, in this training program that has been implemented as a form of the village head's seriousness in empowering women so as to improve the community economy in Air Balui Village